The Relationship of Quarter Life Crisis and Self Confidence with Self Disclosure in Early Adulthood University Students - Faiqotul Himmah; Fathul Lubabin Nuqul; Iin Tri Rahayu (Psychosocia : Journal of Applied Psychology and Social Psychology, 2026)
This study tests a predictive model in which quarter life crisis and self confidence are posited as key factors influencing self disclosure among Indonesian university students in early adulthood. Based on psychosocial development and communication privacy management theories, we hypothesized that a higher quarter life crisis would predict lower self disclosure, while greater self confidence would predict higher self disclosure. Using random sampling, 45 final year students or recent graduates from a large public university were surveyed online. Multiple regression analysis produced the following unstandardized model: Self Disclosure = 30.836 +0.209 (Quarter Life Crisis) + 0.325 (Self Confidence). The overall model was not statistically significant, F (2, 41) = 1.250, P = 0.231, with a low R² of 0.069, explaining only 6.9% of the variance in self disclosure. The weak positive correlation between self disclosure and self confidence (r = .15) and moderate negative correlation between quarter life crisis and self confidence (r = -.45) did not translate into a statistically supported predictive model. Given the non significant result, the limited explanatory power, a small sample size (N = 45), and the moderate reliability of the self confidence measure, the hypothesized model is not supported. This suggests other variables are more influential and future research with larger samples and robust measures is needed to better understand the determinants of self disclosure in this population. Any practical implications for fostering self disclosure as a support strategy therefore remain speculative.